Synthesis of isoxazolin-5-one glucosides by a cascade reaction. - Becker, Tobias; Görls, Helmar; Pauls, Gerhard; Wedekind, Roland; Kai, Marco; Von Reuss, Stephan; Boland, Wilhelm (My University, 2013)
A novel synthetic route was developed for the construction of isoxazolin-5-one glucosides using a cascade reaction. An X-ray crystal structure analysis of a isoxazolin-5-one glucoside confirmed the structure and stereochemistry of the heterocycle. The properties of the α- and β-anomers of the isoxazolin-5-one glucosides were compared. The first synthesis of 2-[6'-(3″-nitropropanoyl)-β-D-glucopyranosyl]-3-isoxazolin-5-one was realized by direct enzymatic esterification without need of further protective groups.